Antwerp X : a combined defense - Armstrong, Clare H. (S.l. : 50 AAA Brigade US Army)
Bibliotheek Camille Huysmans
Dedicator: Armstrong, Clare H., dedicatee: Huysmans, Camille
Engels
Brochure
Keywords: Wereldoorlog 2; Antwerpen